Quantum-Chemical Calculations on the Determination of Chromium (VI) Ion with Two Sodium Salts of 1,8- Dioxynaphthaline 3,6-Disulpho Acid - Bobojonov B.B; Madatov O'.A; Bobojonov X.Sh; Smanova Z.A. (Genius Journals, 2023)
Quantum chemical methods of Gaussian and ORCA software packages were used to calculate the atomic energy of the disodium salt of 1,8-dioxynaphthalene-3,6- disulfoacid, which is used as an analytical reagent for chromium (VI) ions. This reagent contains functionally active and analytically active groups. The geometries of the studied compounds are optimized, the electron density of the molecular orbitals and the total energy of the molecule are calculated
Keywords: Chromium; disodium salt of 1; 8-dioxynaphthalene-3,6- disulfoacid; quantum chemical methods